COMPARISON OF THE FUEL CONSUMPTION STRUCTURE AND POLLUTANT EMISSIONS FOR DETERMINING THEIR REDUCTION DIRECTIONS - Maliarenko, Olena; Eutukhova, Tetyana; Ivanenko, Nataliya; Horskyi, Vitalii; Kobernik, Valentyna (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The relationship between fuel consumption and pollutant emissions in Ukraine for 2013–2021 is compared, graphic dependencies between the fuel used and the emissions of various pollutants across the country and sectors of the economy are revealed, and priority directions for reducing the emissions are proposed. The biggest source of sulfur dioxide emissions is the energy sector, processing and mining industry; emissions of nitrogen oxides – the sectors listed above and agriculture.